CORPORATE SOCIAL RESPONSIBILITY: IMPACT OF CORPORATION ON OUR LIVES - Korontzis, Tryfon Ch. (European Scientific Journal, ESJ, 2013)
In the recent years has been observed that more and more corporations take initiatives in order to contribute actively to the society by making socially responsible acts. With this way they want to contribute in the financial development of the society and also at the same time in the financial growth of the corporation. As social corporate responsibility is defined the voluntary commitment of corporations in order to incorporate to their business practices, social and environmental actions beyond the law and which are related to those affected by them. Corporations ought to make responsible social actions and these are identified in spectrums like human rights, human resources, working conditions, in education, in social activities and in the environment protection. In order social corporate responsibility to function fruitfully in the corporation but also in the society, must be identified with specific policies in the corporation and to its employees, to incorporate in marketing function but at the same time and with its strategies for its development in the market. In this paper we examine the concept of Corporate Social Responsibility and the impact of Corporation on our lives.